2018
DOI: 10.1021/acs.energyfuels.7b03638
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of a Single Char Particle with a Low Ash Fusion Temperature during the Whole Gasification Process

Abstract: The morphological evolution of a single char particle with a low ash fusion temperature (T f) was investigated during the whole gasification process using a high-temperature stage microscope. The experimental results showed that the final shrinkage ratio of char particles at the temperature above T f (1300 °C) was higher than that below the deformation temperature (1000 °C). The transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analysis results showed that the ash distribution in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A small number ofwhat carbon-containing material with high gray was observed on the surface of molten slag. New slag–char interaction characteristics were observed compared with the previous study …”
Section: Results and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A small number ofwhat carbon-containing material with high gray was observed on the surface of molten slag. New slag–char interaction characteristics were observed compared with the previous study …”
Section: Results and Discussionmentioning
confidence: 85%
“…Besides, the critical conversion decreased with the increase of ash content. The critical slag layer thickness was about 6–18 μm for coal chars with different ash contents …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the surface of the char is covered with an ash layer due to the strong CO 2 activation reaction, and the ash layer further hinders the diffusion of CO 2 inside the char. 34 Thus, these factors lead to the formation of an AC sample with a dense surface and poor pore structure.…”
Section: Distribution Of the Pore Structure Of Ac Under Different Conmentioning
confidence: 99%
“…Ding et al in situ analyzed the char-ash/slag transition during char gasification and found that coal rank, ash properties and reaction conditions had great influences on the whole conversion process and the shrinking particle and shrinking core mode were two main reaction modes. Liu et al , proposed a new model of slag-char interaction during gasification and found that the ash was uniformly distributed on char surface when the reaction temperature exceeded the ash deformation temperature. There are many reports on the correlation between the ash change and reactivity.…”
Section: Introductionmentioning
confidence: 99%